Non-invasive through-skull brain vascular imaging and small tumor diagnosis based on NIR-II emissive lanthanide nanoprobes beyond 1500 nm. (July 2018) - Xue, Zhenluan; Zeng, Songjun; Hao, Jianhua
Abstract: Optical bioimaging by using the new short-wavelength infrared window (SWIR, also named as NIR-II, 1000–1700 nm) is emerged as a next generation imaging technique for disease diagnosis owing to the unprecedented improvements in imaging sensitivity and spatial resolution. However, it is challenging to search new imaging agents with highly biocompatible and bright narrow-band emission located in the 1500–1700 nm (referred as NIR-IIb) region. Here we developed high quality polyacrylic acid (PAA) modified NaYF4 :Gd/Yb/Er nanorods (PAA-NRs) with remarkably enhanced NIR-IIb emission and decent bio-compatibility for in vivo cerebral vascular bioimaging and small tumor visualization. These PAA-NRs present efficient narrow-band NIR-IIb emission centered at 1520 with 182 nm of band-width. Owing to the highly efficient NIR-IIb emission, NIR-IIb imaging-guided small tumor (4 mm in diameter) detection is achieved. More importantly, non-invasive optical brain vessel bioimaging with high spatial (∼43.65 μm) and temporal resolution through scalp and skull is obtained without craniotomy. These findings open up the opportunity of designing non-invasive approach for visualization the brain vasculature and tumor in biomedical application.